Flow resistance at lowland and mountainous rivers - Okhravi Saeid; Alemi Mahdi; Afzalimehr Hossein; Schügerl Radoslav; Velísková Yvetta (Journal of Hydrology and Hydromechanics, 2023)
This study initially examines the various sources of flow resistance in sand-bed (lowland) and gravel-bed (mountainous) rivers along with the limitations of traditional estimation methods. The nondimensional hydraulic geometry approach, relating dimensionless flow discharge (q*) to the Darcy-Weisbach friction factor (f), has demonstrated good performance for both river types, covering shallow to moderately deep flows. However, accuracy in estimating f is affected by simplifications like assuming uniform and deep flow, neglecting bed load transport and vegetation effects, which require further evaluation. To address these issues, the proposed method is evaluated using data from four sand-bed rivers in Slovakia (with vegetation), and three gravel-bed rivers in Iran (dominated by cobbles and boulders). Bedforms prove to be significant resistance sources in all studied rivers. The approach yields separate predictors for each river type, showing a satisfactory agreement between observed and calculated values within a maximum deviation of ±20% error bands. These predictors are further validated using field data and established equations from rivers with similar physiographic characteristics. Results indicate the method performs well in predicting flow resistance in sand-bed rivers, slightly overestimating overall (+40%). It effectively captures riverbed features and vegetation influence under small-scale roughness conditions. However, the predictor’s validity for gravel-bed rivers is somewhat limited due to high variability in water-surface profiles, making it challenging to accurately capture flow dynamics under large-scale roughness conditions. Addressing complex characteristics of gravel-bed riverbeds, including boulders and local energy extraction, is crucial for improving the estimation of water-surface profile variations and flow resistance using the hydraulic geometry approach.